FAKTOR RESIKO NEUROPATI PERIFER DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 : TINJAUAN LITERATUR - Rima Novia Putri; Agung Waluyo (LPPM Universitas Abdurrab, 2020)
Type 2 diabetes mellitus is one of the chronic diseases that has increased globally and is a cause of various organ dysfunction such as diabetic peripheral neuropathy. Early detection of diabetic peripheral neuropathy and identification of risk factors can reduce the morbidity of diabetic peripheral neuropathy. This literature review was written to present the risk factors of diabetic peripheral neuropathy in type 2 diabetes mellitus patients. Literature search was conducted to obtain appropriate articles through the electronic database Medline, Cinahl, Proquest, and Clinical Key with keywords: prevalence of diabetic peripheral neuropathy, risk factors and type 2 diabetes mellitus. The results obtained 16 articles according to the topic and through a review, it is known that risk factors of diabetic peripheral neuropathy in type 2 diabetes mellitus patients are old age, male sex, duration of diabetes mellitus, poor glycemic control, retinopathy, nephropathy, and risk factors of cardiovascular diseases such as: obesity, overweight, hypertension,and dyslipidemia.